2006
DOI: 10.1111/j.1471-0528.2006.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Gynaecological oncology: The role of colposcopy in the follow up of women treated for cervical intraepithelial neoplasia

Abstract: Objective To determine the effect of colposcopy on the sensitivity and specificity of follow-up procedures in the detection of residual or recurrent disease after treatment for cervical intraepithelial neoplasia (CIN).Design A retrospective study of information held in a colposcopy database.Setting A teaching hospital colposcopy clinic. Main outcome measures The sensitivity and specificity of cytology alone was compared with the sensitivity and specificity of the combination of colposcopy and cytology.Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
0
14
0
6
Order By: Relevance
“…Soutter et al [8] in a large patient analysis of women after loop biopsy found that addition of colposcopy to cytological surveillance in the follow-up schedule of high-risk women would have identified only 13 extra cases of high-grade CIN with 76 extra false positives per 1,000 women. These authors recommend prolonged colposcopic follow-up for this high-risk group, suggesting that colposcopy would identify recurrent CIN earlier; not that cytological surveillance would miss disease, but would take about 5 annual smears to reduce undetected post-treatment disease to 1%.…”
Section: Discussionmentioning
confidence: 98%
“…Soutter et al [8] in a large patient analysis of women after loop biopsy found that addition of colposcopy to cytological surveillance in the follow-up schedule of high-risk women would have identified only 13 extra cases of high-grade CIN with 76 extra false positives per 1,000 women. These authors recommend prolonged colposcopic follow-up for this high-risk group, suggesting that colposcopy would identify recurrent CIN earlier; not that cytological surveillance would miss disease, but would take about 5 annual smears to reduce undetected post-treatment disease to 1%.…”
Section: Discussionmentioning
confidence: 98%
“…[8], en un amplio análisis de mujeres tras una biopsia con asa, observaron que la adición de la colposcopia a la vigilancia citológica en la pauta de seguimiento de las mujeres de alto riesgo hubiera identificado tan solo 13 casos adicionales de CIN de alto grado, con 76 falsos positivos adicionales por cada 1.000 mujeres. [8], en un amplio análisis de mujeres tras una biopsia con asa, observaron que la adición de la colposcopia a la vigilancia citológica en la pauta de seguimiento de las mujeres de alto riesgo hubiera identificado tan solo 13 casos adicionales de CIN de alto grado, con 76 falsos positivos adicionales por cada 1.000 mujeres.…”
Section: Discussionunclassified
“…Las mujeres con antecedente de CIN2+ tratado o con resolución espontánea en los últimos 20 años siguen teniendo un riesgo de sufrir un CCU entre 5 y 10 veces mayor que la población general 128,129 . Por esta razón, en muchos países se recomienda el seguimiento más frecuente en los primeros años postratamiento y seguir con cribado citológico cada 3 años o con prueba de VPH o co-test cada 5 años hasta los 20 años, independientemente de que la mujer haya cumplido los 65 años 47,69,130 .…”
Section: Justificaciónunclassified